(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, the prospects for improving the financing system of fruit and vegetable clusters are widely discussed. Fruit and vegetable clusters are highly effective in finding and introducing innovations suitable for our regions and climate. This research intends to conduct an econometric analysis of the influence of factors on the productivity of vegetable products and fruit products. Conclusions and proposals were also developed on the prospects of improving the financing system of fruit and vegetable clusters.